Socialization of The Dangers of Gadget and Internet Use for Children: Qualitative Study from SD Negeri 2 Lilialy, Buru Regency, Maluku, Indonesia - Anwar, Arman; Buton, Fatmi (Manunggal Halim Jaya, 2025)
Socialization about the impact of gadget and internet use on elementary school children is important considering their high exposure to technology from an early age. This study aims to improve the understanding of students of SD Negeri 2 Lilialy regarding the positive and negative impacts of gadget use, as well as to encourage wiser use. Socialization was carried out through lecture methods, group discussions, and simple simulations. The results of the study showed that before socialization, around 60% of students used gadgets for entertainment without understanding the risks involved. After socialization, there was an increase in understanding, where 85% of students were able to mention negative impacts such as dependence, physical health problems, and the risk of exposure to inappropriate content. This activity proves that interactive methods are effective in helping students understand the dangers of excessive gadget use and how to manage their use in a healthy way. Thus, ongoing socialization and more intensive digital literacy programs are expected to encourage students to use technology wisely.